2018
DOI: 10.3847/1538-4357/aaa1eb
|View full text |Cite
|
Sign up to set email alerts
|

The Large-scale Coronal Structure of the 2017 August 21 Great American Eclipse: An Assessment of Solar Surface Flux Transport Model Enabled Predictions and Observations

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The model employs two key innovations: a physicsbased formulation that describes the heating of the corona over a broad range of conditions, and a novel approach for energizing the coronal magnetic field on global scales. A related prediction of this eclipse with a different model has also been made 19 , and is discussed below.…”
Section: Introductionmentioning
confidence: 97%
“…The model employs two key innovations: a physicsbased formulation that describes the heating of the corona over a broad range of conditions, and a novel approach for energizing the coronal magnetic field on global scales. A related prediction of this eclipse with a different model has also been made 19 , and is discussed below.…”
Section: Introductionmentioning
confidence: 97%
“…A composite of our images has been used to successfully compare with the predictions (Mikic et al, 2018) made preeclipse on the basis of the prior month of magnetograms of the solar disk from the HMI instrument on NASA's Solar Dynamics Observatory. Nandy et al (2018) used a solar-surface flux-transport model for predicting the coronal configuration.…”
Section: Observations and Methodsmentioning
confidence: 99%
“…Testing these theoretical modeling approaches through "true" predictions and constraining them through observations is best achieved at the time of solar eclipses when lunar occultation masks the bright solar disk revealing the Sun's faint coronal structure. In an earlier work, Nandy et al (2018) postulated a novel methodology for long-term coronal field prediction. Posteclipse assessment demonstrated that they successfully predicted all the major large-scale structures of the great American solar eclipse (2017 August 21) including a pseudostreamer that was not captured in an alternative prediction methodology (Mikić et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Posteclipse assessment demonstrated that they successfully predicted all the major large-scale structures of the great American solar eclipse (2017 August 21) including a pseudostreamer that was not captured in an alternative prediction methodology (Mikić et al 2018). Nandy et al (2018) used a data-driven Predictive Solar Surface Flux Transport (PSSFT) model developed at the Center of Excellence in Space Sciences India (CESSI; to first predict the surface magnetic field distribution and then feed this into a potential field extrapolation model to obtain the prediction of the coronal magnetic field structure. The PSSFT model simulates the evolution of the surface magnetic field driven by the emergence of tilted active regions and redistribution of associated magnetic flux mediated via large-scale plasma flows and supergranular diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation